Preliteracy Skills in Primary-Aged English Language Learners - Amy Davis (The Advocate, 2018)
This paper describes the transition of English language learners acquiring preliteracy skills in learning to read and the role of productive and receptive language in the development of phonological awareness. As English language learners transition to reading to learn, oral reading fluency becomes an important component of future reading success. Because of the lack of resources, print and language exposure, students acquiring a second language face the challenge of becoming successful readers.